Electroneuromyography for early diagnosis of diabetic distal polyneuropathy - Elena S. Mazurenko (Endocrinology Research Centre, 2019)
BACKGROUND: Diabetic distal polyneuropathy (DDPN) is a predictor of diabetic foot syndrome development, ulcer formation and lower limb amputation. An early DDPN diagnosis is therefore relevant. AIM: To investigate the effectiveness and suitability of electroneuromyography (ENMG) for early DDPN diagnosis. MATERIALS AND METHODS: This study was performed in the Novosibirsk Research Institute of Traumatology and Orthopaedics n.a. Ya. L. Tsivyan. A total of 80 participants were examined, including 30 DM2 patients, 30 patents without carbohydrate metabolism disorders, and 20 healthy volunteers aged 20–30 years. None of the participants showed clinical signs of distal polyneuropathy (DPN). All participants underwent evaluation of neuropathy symptoms by the Neuropathy Symptom Score scale, neurological assessment using on the scale of Neuropathic Dysfunctional Score and stimulating ENMG. RESULTS: ENMG revealed the presence of neuropathy in 86.7% of DM2 patients. Moreover, among DM2 patients, 12 (40%) presented sensory DDPN, 13 (43.3%) presented sensorimotor neuropathy and 1 (3.3%) presented motor DDPN. The medial and lateral plantar nerves were the most commonly affected (p = 0.018 and p = 0.002, respectively). Among the 30 control individuals, 9 (30%) showed signs of DPN in combination with radiculopathy. ENMG - indicators of DDPN: latency and amplitude and speed for 3 sensory (n. Plantaris lateralis, n. Plantaris medialis, n. Suralis) and 2 motor nerves (n. Peroneus, n. Tibialis) were significantly worse in individuals with DM2 than in the control group, both for those with and without radiculopathy. Among participants with DM2, those sensorimotor DDPN tended to have a longer diabetes duration (p = 0.503), higher levels of HbA1c (p = 0.077) and higher BMI (p = 0.050) than those with sensory neuropathy, although the differences were not significant. CONCLUSION: This study confirms the effectiveness and suitability of ENMG for the early diagnosis of DDPN. Moreover, the optimal ENMG indices necessary for this diagnosis were identified.